2015
DOI: 10.1016/j.intimp.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pain in fibromyalgia patients with testosterone gel: Pharmacokinetics and clinical response

Abstract: To test our hypothesis that testosterone deficiency plays an important role in chronic pain, a Phase I/II pilot study was initiated with 12 fibromyalgia patients to verify that a daily dose for 28days with transdermal testosterone gel would 1) significantly and safely increase mean serum testosterone concentrations from low baseline levels to mid/high-normal levels, and 2) effectively treat the pain and fatigue symptoms of fibromyalgia. Pharmacokinetic data confirmed that serum free testosterone concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 34 publications
(39 reference statements)
1
22
0
2
Order By: Relevance
“…There is little experimental evidence in chronic pain conditions on this topic, and exogenous modulators of sex hormones could act differently than normally cycling hormones. We noted cases where sex hormones were administered systemically 44 or locally 32 to reduce pain and/or inflammation, and the use of sex hormones in treating autoimmune pain disorders is still a topic of interest. 17 Effects of administered sex hormones on pain has also been studied in the context of transsexual individuals receiving hormone treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little experimental evidence in chronic pain conditions on this topic, and exogenous modulators of sex hormones could act differently than normally cycling hormones. We noted cases where sex hormones were administered systemically 44 or locally 32 to reduce pain and/or inflammation, and the use of sex hormones in treating autoimmune pain disorders is still a topic of interest. 17 Effects of administered sex hormones on pain has also been studied in the context of transsexual individuals receiving hormone treatment.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, it has been posited that the sex hormone testosterone may provide a protective effect for men against these types of chronic pain disorders 7 with transdermal testosterone gel significantly reducing fibromyalgia pain in women. 44…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional populationbased study revealed that a higher estradiol/testosterone ratio associated significantly with autoimmune thyroid disease among Chinese men (Chen et al, 2017). Interestingly, a clinical phase I/II pilot study among 12 female FMS patients revealed that a 28-day treatment with testosterone gel significantly decreased pain, stiffness, and fatigue (White et al, 2015). Altogether, the efficacy of the thymus depends strongly on age and sex hormones.…”
Section: Sex Differences In Immune Tolerancementioning
confidence: 99%
“…Для женщин характерна зависимость симптоматики от уровня их колебания в крови. Так, D. White [37] показал эффективность ЗГТ гелевой формой тестостерона у женщин 44-53 лет с СФ в виде значительного уменьшения выраженности болевого синдрома и мышечной утомляемости. Тестостерон способствовал повышению устойчивости к мышечным нагрузкам и уменьшал восприятие боли.…”
Section: синдром фибромиалгии (сф)unclassified
“…Выраженность боли у женщин меняется в зависимости от фазы менструального цикла, хотя не ясно, какая фаза связана с большим количеством болевых симптомов. [30,37]. У женщин пик заболеваемости РА приходится на возраст 40-50 лет, когда происходит снижение уровня женских половых гормонов, в том числе обладающих протективным действием на хрящ эстрогенов.…”
Section: ревматоидный артрит (ра)unclassified